Imide arylation with aryl(TMP)iodonium tosylates - Basu, Souradeep; Sandtorv, Alexander H.; Stuart, David R. (Beilstein Journal of Organic Chemistry, 2018)
Herein, we describe the synthesis of N-aryl phthalimides by metal-free coupling of potassium phthalimide with unsymmetrical aryl(TMP)iodonium tosylate salts. The aryl transfer from the iodonium moiety occurs under electronic control with the electron-rich trimethoxyphenyl group acting as a competent dummy ligand. The yields of N-aryl phthalimides are moderate to high and the coupling reaction is compatible with electron-deficient and sterically encumbered aryl groups.
Keywords: arylation; C–N coupling; diaryliodonium; hypercoordinate iodine; metal-free

(untitled) - Wishart, D. S.; Feunang, Y. D.; Guo, A. C.; Lo, E. J.; Marcu, A.; Grant, J. R.; Sajed, T.; Johnson, D.; Li, C.; Sayeeda, Z.; Assempour, N.; Iynkkaran, I.; et al. (Nucleic Acids Res., 2018)

(untitled) - Fujiwara, T.; O’Hagan, D. (J. Fluorine Chem., 2014)

(untitled) - Breugst, M.; Tokuyasu, T.; Mayr, H. (J. Org. Chem., 2010)

(untitled) - Jadhav, B. D.; Pardeshi, S. K. (RSC Adv., 2016)

(untitled) - Payen, O.; Top, S.; Vessières, A.; Brulé, E.; Plamont, M.-A.; McGlinchey, M. J.; Müller-Bunz, H.; Jaouen, G. (J. Med. Chem., 2008)

(untitled) - Deprez, N. R.; Sanford, M. S. (Inorg. Chem., 2007)

(untitled) - Merritt, E. A.; Olofsson, B. (Angew. Chem., Int. Ed., 2009)

Hypervalent Iodine Chemistry - Olofsson, B. (Arylation with Diaryliodonium Salts, 2016)

(untitled) - Aradi, K.; Tóth, B. L.; Tolnai, G. L.; Novák, Z. (Synlett, 2016)

(untitled) - Stuart, D. R. (Chem. – Eur. J., 2017)

(untitled) - Lucchetti, N.; Scalone, M.; Fantasia, S.; Muñiz, K. (Angew. Chem., Int. Ed., 2016)

(untitled) - Seidl, T. L.; Sundalam, S. K.; McCullough, B.; Stuart, D. R. (J. Org. Chem., 2016)

(untitled) - Sandtorv, A. H.; Stuart, D. R. (Angew. Chem., Int. Ed., 2016)

(untitled) - Seidl, T. L.; Stuart, D. R. (J. Org. Chem., 2017)

(untitled) - Phan, T. B.; Mayr, H. (J. Phys. Org. Chem., 2006)

(untitled) - Mayr, H.; Ofial, A. R. (Acc. Chem. Res., 2016)